2019
DOI: 10.1186/s12887-018-1388-0
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent-parent communication on sexual and reproductive health issues and its factors among secondary and preparatory school students in Hadiya Zone, Southern Ethiopia: institution based cross sectional study

Abstract: BackgroundAdolescent communication with parents is paramount to reduce sexual health problems. Currently, there is a shortage of information on adolescent-parent communication in Ethiopia in general and study area in particular. Thus, this study is intended to determine adolescent-parent communication on sexual and reproductive health issues and its factors among secondary and preparatory school adolescents in Hadiya Zone, Ethiopia.MethodsWe used institution based cross-sectional study design. We stratified sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
69
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 25 publications
15
69
0
4
Order By: Relevance
“…Providers in the study repeatedly complained lack of discussion between adolescents and parents. This nding agrees with the studies in India [20], Kenya [30] and Nigeria [31] and Ethiopia [32,33]. Other studies also indicated that lack of parental knowledge and positive control [32] as well as gender-selective in uence [34] and poor parental involvement in planning SRHs [35,36] barriers to accessing services.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Providers in the study repeatedly complained lack of discussion between adolescents and parents. This nding agrees with the studies in India [20], Kenya [30] and Nigeria [31] and Ethiopia [32,33]. Other studies also indicated that lack of parental knowledge and positive control [32] as well as gender-selective in uence [34] and poor parental involvement in planning SRHs [35,36] barriers to accessing services.…”
Section: Discussionsupporting
confidence: 89%
“…Because, I see that adolescents are in uenced by peers not by theirs own decision." [Female, Age:[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Health Extension] Another participant witnessed disclosing secrecy of adolescents from his experience. "Healthcare providers have a problem of keeping secrets about adolescent and sexual issues.…”
mentioning
confidence: 99%
“…After 36 months, study participants in the treatment groups were less likely to have an STI and unprotected sex at last sexual encounter comparable to their counterparts in the two control conditions (62). This finding underscores the need to improve adolescent-parent communication and information sharing (63). This communication approach helps adolescents to establish individual values toward healthy sexual behaviors such as abstinence, improved contraception, how to prevent HIV, and other sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 79%
“…Studies published from January 2000 to June 2020 were included in the systematic review and meta-analysis. The included studies were conducted in 5 Regions of Ethiopia; Amhara Region [ 12 , 14 , 18 , 19 , 25 ], Oromiya Region ([ 23 , 29 ]; Feyisa M: Parent-adolescent Sexual and Reproductive Health Communication and Associated Factors Among Secondary And Preparatory School Students In Fiche Town, North Shoa, Oromia Regional State, unpublished), Southern Nations Nationalities and People Region (SNNPR) [ 15 , 20 – 22 ], Tigray Region [ 24 ] and the capital Addis Ababa [ 26 ] see detail (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%